Complexity of long-term psychological effects of political repressions in Lithuania - Kazlauskas, Evaldas; Gailienė, Danutė (Psichologija, 2003)
OBJECTIVE: This study examined long-term consequences of political repressions during the Soviet regime in Lithuania. Between 1940 and 1958 more than 300,000 Lithuanians were arrested and deported to Siberia (Anušauskas, 1996). Conditions of imprisonment in Gulag camps were extremely hard and mortality rate from exhaustion and disease was high. Victims who managed to return back to Lithuania suffered from persistent persecutions. Traumatic experiences of former political prisoners were neglected for decades; they had to keep in secret the fact of the imprisonment. Less than 5,000 survivors of political imprisonment still live in Lithuania. Since the introduction of posttraumatic stress disorder in DSM-III (1980) trauma effects have been studied mostly in terms of posttraumatic stress disorder (PTSD). But clinicians and trauma researchers acknowledge controversies in modern understanding of PTSD (Yahuda, MacFarlane, 1995). Severe impairments in personality of victims have been reported by clinicians working with survivors of holocaust, sexual abuse, and victims of torture, but these changes in personality are not accepted in current understanding of PTSD. The concept of PTSD receives more and more critics due to limitations in describing psychological effects after long term traumatic experiences that may lasts for years. Complex posttraumatic stress disorder has been introduced (Herman, 1992) in result of these discussions to describe variety of effects of long term trauma, and acceptance of this concept is growing in the field. There are only few studies on psychological effects of political repressions in former Soviet Union territory. This is the first study of psychological effects of political imprisonment in Lithuania. The goal of present study was to examine traumatic experiences and psychological effects among non-clinical sample of former Lithuanian political prisoners. METHOD: The group of former political prisoners (N=50), with a history of deportation to Gulag camps, was compared with an age and sex matched control group (N=50). Former political prisoners were imprisoned for 6.9 years on average. 43.1 years have passed since their return to Lithuania at a time of research. Semi-structured interviews were used to measure experiences during and after imprisonment. Posttraumatic effects were measured using Lithuanian versions of self-rating scales: Harvard Trauma Questionnaire (Mollica et al., 1992), Impact of Event Scale - Revised (Weiss, Marmar, 1996), Trauma Symptom Checklist (Briere, Runtz, 1989). CONCLUSIONS: Results suggest that traumatic experiences dealing with political imprisonment and exile have long-term complex posttraumatic effects on Lithuanian former political prisoners. Concept of complex posttraumatic disorder is partly supported by results of this study. Limitations of the study due to retrospective nature of the study, elderly age of participants and control group selection are discussed. Further research is required to assess the impact of political oppression during Soviet regime on population of former Soviet Republics.